An efficient and no pollutants deproteinization method for polysaccharide from Arca granosa by palygorskite adsorption treatment. (20th July 2019) - Li, Wei; Liu, Junying; Su, Jiaxian; Wu, Jun; Xia, Yalan; Zhu, Lijun; Xu, Zhanchi; Zhao, Weibo; Yan, Yajuan; Zhang, Danyan
Abstract: The purpose of this study was to develop an efficient and no pollutants deproteinization method for polysaccharide (AGP) from Arca granosa based on the palygorskite adsorption treatment (PAT). Firstly, the optimal adsorption conditions were obtained by the response surface methodology (RSM) as follows: adsorption for 136 min at 60 °C with the dosage of 0.27 g. Under the optimal conditions, the deproteinization ratio ( Dr% ), recovery ratio ( Rr% ) and selectivity coefficient ( K C ) were 87.35 ± 0.44%, 92.89 ± 0.41% and 12.28 ± 0.64, respectively. Then, the adsorption kinetics and isotherms experiments indicated that the adsorption process was endothermic and spontaneous, and were fitted well by the pseudo-second-order equation and the Freundlich equation, respectively. In addition, compared with the classical Sevag method, the PAT method was proven to be reliable. More importantly, the palygorskite was reusable and the deproteinization process produced no pollutants. These results demonstrated that the PAT method present a highly efficient and environmental friendly technique for the large-scale deproteinization of polysaccharides. Graphical abstract: An efficient and no pollutants deproteinization method based on the palygorskite adsorption treatment (PAT) was developed successfully. The adsorption conditions, adsorption behaviors, and the reusability were investigated, respectively. In addition, the reliable of the PAT method was studied by compared with the Sevag method.Image 1 Highlights: Palygorskite adsorption deproteinization is proven effective and reliable. Adsorption conditions of palygorskite adsorption treatment (PAT) are optimized. The fundamental adsorption behaviors of the PAT method are investigated. The PAT method is no pollutants and suitable for large-scale deproteinization.